ASSESSMENT CARTS STRENGTH INDICATORS WAGONS WITH EXPIRED SERVICE LIFE (Transport systems and technologies, 2021)
Currently, a significant number of units of specialized cars of 1520 mm gauge in Ukraine has a service life that exceeds that assigned by the manufacturer. At the same time, many years of experience in diagnosing and analyzing the operation of carts of these cars by specialized organizations, shows that their technical condition after long operation shows that the specified service life specified in the technical conditions in most cases far from the limit. This is largely due to the significant margin of safety, which is laid down in the design, and the peculiarities of the operation of a particular type of car. The paper considers the issues of assessing the operation of such cars on the example of the carriage of the weighing car, bogie model 18-102, and the carriage of the passenger car model KVZ-TsNII used in the track economy for transportation of workers. The average daily mileage of such cars is 60-70 percent less than the average mileage that is laid down when calculating the service life assigned by the manufacturer. The evaluation and methods of determining the strength of the frames of carriages of special cars are performed. Conclusions are made based on the results of the analysis of the strength of the carriages of special cars.
Keywords: bogies, control tests, resource, technical diagnostics, safety margin, resource estimation, strength.